RESEARCH ON THE MUSICAL CHARACTERISTICS AND SINGING STYLE OF ZHENBA FOLK SONGS IN CHINA - Meng Na; Azli Ariffin, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
As a carrier of traditional culture, Zhenba folk songs have faced a serious impact from modern media in recent years. Contemporary young people are more fond of pop songs, resulting in Zhenba folk songs gradually losing the new generation of successors and singers. This problem is especially urgent when most of the original singers are now in their old age. In order to cope with this cultural crisis, this study aims to systematically analyse the characteristics, classification, musical features and singing styles of Zhenba folk songs, as well as to explore in depth the issues of their history, development and inheritance, in order to comprehensively understand the process of the emergence and evolution of this musical form. This study adopts the research method combining literature analysis method, field survey method and music analysis method. The literature analysis method is mainly used to collate and analyse the existing research results of Zhenba folk songs; the field survey method collects first-hand information through field visits to Zhenba County; and the music analysis method reveals the musical characteristics of the folk songs through the analysis of their scores. Through comprehensive analyses from multiple perspectives and levels, this study seeks to reveal the unique value of Zhenba folk songs in traditional culture and the realistic challenges they face. Through the combination of literature analysis, fieldwork and music analysis, the study will not only provide a deeper understanding of the cultural connotations and musical characteristics of Zhenba folk songs, but also provide practical suggestions and countermeasures for their inheritance and protection.